Sustainable rural tourism: An indigenous community perspective on positioning rural tourism - Shaista, Falak; Yeo, A.W; Lo, May-Chiun (Institut za turizam, 2016)
It is commonly assumed that formulation of tourism policies and the marketing of destination areas are dictated by the needs and interests of visitors. Often ignored however, are the views of the local communities, the roles they play in these processes as well as the impacts on the indigenous communities and their socio-cultural spaces. Th us this paper presents a study conducted with the indigenous community of Long Lamai in Malaysia, who has recently ventured into rural tourism. Th e Long Lamai community has slowly transformed from being solely dependent on hunting gathering to leveraging on their rich natural sources for a cash income as well as opening up to the outside world. Th e local community perceives tourism as the best option to sustain and align their lifestyle to their new needs. However as a remote community, they are also aware of the vulnerabilities due to the rapid development plans which may bring about adverse eff ects to their present healthy existence. Th e purpose of this study was twofold: (1) to assess the local community's support for tourism development: and (2) to explore the perceived positioning of rural tourism by local people. Results showed that the majority of community members have strong support for tourism development and they are also ready to face possible challenges that come with this development. Major concern s expressed by community members include environmental conservation and local cultural protocols.